PELATIHAN MARKETING PLAN BAGI PENGRAJIN SANGGAR MELATI DI KOTA BATAM - Yuanita FD Sidabutar; Angelina Eleonora Rumengan; Malahayati Rusli Bintang; Mohamad gita Indrawan; Raymond (LPPM-Universitas Batam, 2023)
This community service is carried out with the aim of improving the Marketing Plan capabilities of Jasmine studio craftsmen. In this Marketing Plan Training, it will be carried out using a direct guidance method by providing material and input on obstacles faced related to marketing issues. The